CHILEAN SOCIALIST ACTIVISM AND RESISTANCE BETWEEN 1973 AND 1975:A STORY OF SACRIFICE - Blasco Rovira, Anna; Sierpe, Vladimir (Revista de Historia Social y de las Mentalidades, 2015)
From 1973 until 1975 the first clandestine leadership of the PSCH (Chilean Socialist party) was active in Chile, mainly in the Capital Santiago. Through the methodological tools of Collective Behavior and Social Movements’ sociology, we aim to explain how and why a group of young socialists was politically active until their very end. In other words, how the network structure, in a particularcontext, created the conditions of the sacrifice of the network’s actors.We plan to analyze historical context as well as actors’ socialization processes. Based on historical facts and events we will try to present their political pathways which ended with their disappearances and deaths. Methodologically, we are presenting different types of sources and data, mainly oral ones, which were gathered by scholars from Chile and from other countries. Doing so we can present here the conditions and characteristics of one socialist group’s activism. We deal chronologically with the various facts and events in order to underline the political dimension of their activities